2012
DOI: 10.14569/ijacsa.2012.031007
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy to Improve The Usage of ICT in The Kingdom of Saudi Arabia Primary School

Abstract: Abstract-Integration of ICT in education is a complex idea that requires practical interpretation to get significant outcomes. As a developing country, the Kingdom of Saudi Arabia (the KSA) does not have a proper technological infrastructure as developed countries. Efficient strategies are vital in improving the application of ICT in the KSA's primary schools effectively. Improving the usage of ICT in the KSA primary schools achievement entails integrating ICT into classroom. However, some barriers that preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…It follows logically that the use of ICT at the primary level would prepare the children from the very early stage of education to enable them to use ICT with confidence by the time they reach secondary school. However, effective strategies critical to the introduction and usage of ICT in Saudi primary schools are not currently in place [26].…”
mentioning
confidence: 99%
“…It follows logically that the use of ICT at the primary level would prepare the children from the very early stage of education to enable them to use ICT with confidence by the time they reach secondary school. However, effective strategies critical to the introduction and usage of ICT in Saudi primary schools are not currently in place [26].…”
mentioning
confidence: 99%
“…In his study, Khan (2001) found that the lecturers and trainers' competency could be enhanced on technology when they made use of various ICT-based hardware and software. It will give them the capability to deliver a more enhanced graphics-oriented presentation of lectures (Ageel & John, 2012, p. 2), facilitate computer based technologies for knowledge sharing (Lindvall & Rus, 2003, p. 4), change the ways of teaching (Almalki & Williams, 2012, p. 3) deliver high quality education and prepare students for the information era (AbdulKafi, 2006, p. 5), and help reduce teachers' efforts to deliver knowledge, achieve better visualization and motivate the learners (Almalki & Williams, 2012, p. 1).…”
Section: Saudi Arabian Contextmentioning
confidence: 99%
“…From his findings, it is Saudi headmasters who should assume technology leadership. Almalki and Williams (2012) claim that technology leadership cannot be separated from a suitable ICT infrastructure environment and training, which is strategic to Saudi ICT-related reform across all stages of education.…”
Section: The Concept Of Technology Leadership In Saudi Arabiamentioning
confidence: 99%